The application of professional standards on the example of financial market specialists - S. V. Brovchak (Путеводитель предпринимателя, 2020)
The article deals with the application ofprofessional standards on the example of qualifications of insurance market specialists, as well as their interface on the basis of the interstate register of qualifications, monitoring of the labor market, approval of qualification requirements.